Highly Conductive Bimetallic Ni–Fe Metal Organic Framework as a Novel Electrocatalyst for Water Oxidation - Zheng, Fuqin; Xiang, Dong; Li, Ping; Zhang, Ziwei; Du, Cheng; Zhuang, Zhihua; Li, Xiaokun; Chen, Wei (ACS sustainable chemistry & engineering, 2019)
In recent years, metal–organic frameworks (MOFs) have been extensively investigated for diverse heterogeneous catalysis due to their diversity of structures and outstanding physical and chemical properties. Currently, most related work focuses on employing MOFs as porous substrate materials to fabricate confined nanoparticle or heteroatom-doped electrocatalysts which have to be annealed at high temperature before application. However, the annealing process would destroy the structure completely and lose the intrinsic active sites in MOFs framework. Herein, a simple solvothermal process is used to synthesize a series of Fe/Ni bimetallic MOFs. The as-prepared MOFs are applied directly as highly efficient oxygen evolution reaction (OER) electrocatalysts with no post-annealing treatment. The bimetallic FeNi-MOFs show higher OER activity than single metal MOFs and commercial precious RuO2 catalysts. With the optimized FeNi-MOF as the catalyst, the OER current densities of 50 and 100 mA/cm2 can be achieved at the overpotentials of only 270 and 287 mV, respectively. Meanwhile, a small Tafel slope of 49 mV/dec was obtained. Moreover, this catalyst shows high electrochemical stability in strong basic solution. This work demonstrates that through structural optimization, bimetallic and multimetallic MOFs may have promising potentials as advanced catalysts for electrochemical energy conversion.